T-cell immune status in patients with acute exacerbation of chronic obstructive pulmonary disease: a case-control study - Xiao-feng Xiong; Xiao-feng Xiong; Min Zhu; Min Zhu; Hong-xia Wu; Zuo-hong Wu; Li-li Fan; De-yun Cheng (Frontiers in Medicine)
IntroductionImmune inflammatory response plays an important role in chronic obstructive pulmonary disease (COPD). However, the cellular immune status of patients with COPD at different phases is unclear. Herein, we aim to investigate the distribution and functional status of T cell subsets in different phases of COPD (acute exacerbation of COPD [AECOPD] and stable COPD [SCOPD]).MethodsThis is an observational case-control study undertaken in West China Hospital. The distribution of T cell subsets in peripheral blood of AECOPD, SCOPD, and healthy controls (HCs) was measured using multi-color flow cytometry, and the functional status was analyzed by additional staining of activation markers.ResultsA total of 43 HCs, 43 SCOPD patients, and 64 AECOPD patients were evaluated. The total number and percentage of lymphocytes and the CD4+/CD8+ T cells ratio were significantly lower in AECOPD patients when compared to HCs. HLA-DR expression in CD3+, CD4+, CD8+, CD8+ TCR aβ, and CD4+ TCR aβ T cells was upregulated in the AECOPD group. Similarly, the expressions of HLA-DR, CD57, and PD-1 were higher in T cell subsets in the AECOPD group. Compared with the SCOPD and HC groups, the AECOPD had a significantly lower proportion of CD4+CD27+CD28+ T cells, but opposite results were found for CD4+CD27-CD28- T cells. In addition, the proportion of CD4+CD39+ T cells and CD4+CD25+FoxP3+ T cells was significantly higher in the AECOPD and SCOPD groups when compared to the HC group (P < 0.05).DiscussionThe distribution of nearly half the T cell subsets in AECOPD patients was significantly different from that in SCOPD patients and HCs. AECOPD patients may have cellular immune suppression, immune dysfunction, abnormal activation, and higher senescence depletion of T cells.